2005
DOI: 10.1207/s15324796abm3003_2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-monitoring, outcome expectancies, difficulties with eating and exercise, and physical activity and weight loss treatment outcomes

Abstract: Interventions that are targeted to increase self-monitoring and to improve transient difficulties with exercise and diminished outcome expectancies may improve BWLP treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 24 publications
4
100
0
Order By: Relevance
“…Self-monitoring exercise has been shown to be related to weight loss. 15 Most trials examining PA self-monitoring frequency have used paper journals for self-monitoring. 4 In one of the few behavioral weight loss studies examining mobile PA self-monitoring, researchers found that a wearable, mobile sensor to self-monitor PA enhanced a behavioral weight loss intervention over no electronic PA monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Self-monitoring exercise has been shown to be related to weight loss. 15 Most trials examining PA self-monitoring frequency have used paper journals for self-monitoring. 4 In one of the few behavioral weight loss studies examining mobile PA self-monitoring, researchers found that a wearable, mobile sensor to self-monitor PA enhanced a behavioral weight loss intervention over no electronic PA monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support several studies that have shown a positive association between self- monitoring and PA change. [58][59][60][61][62] In the present study, the Fitbit tracker allowed participants to access quick readings of their PA performance throughout the day. It is unclear as to why comparison participants were more engaged compared with those in the intervention.…”
Section: Self-monitoring (Fitbit One) Onlymentioning
confidence: 99%
“…34,42 In conjunction with self-monitoring that allows AYAs to identify patterns of exercise and barriers to engagement, problem-solving skills training to generate solutions to identified barriers is also a well-supported strategy to improve health behavior engagement in several chronic illness groups. 63 Problem-solving skills training generally consists of the following components: defining the problem, generating alternative solutions, deciding on a solution, and implementing and evaluating the solution. Providing AYAs with the skills to systematically think through any barriers or issues they experience when attempting to exercise will not only allow them to work through these barriers, but it will provide them with the skills necessary to independently think through barriers that may arise in the future.…”
Section: Problem-solving Skills Trainingmentioning
confidence: 99%